1999
DOI: 10.1128/mcb.19.5.3580
|View full text |Cite
|
Sign up to set email alerts
|

Rho3 of Saccharomyces cerevisiae, Which Regulates the Actin Cytoskeleton and Exocytosis, Is a GTPase Which Interacts with Myo2 and Exo70

Abstract: E129,A131 , which causes a morphological abnormality, was expressed. These results provide a direct molecular basis for the action of Rho3 on exocytosis and the actin cytoskeleton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
179
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(192 citation statements)
references
References 63 publications
10
179
0
3
Order By: Relevance
“…Thus, the multiple, and likely regulated, association of exocyst with various cellular structures may play a role in coordinating protein synthesis, vesicle trafficking and cytoskeletal organization to promote cell growth and cell differentiation. Furthermore, some potential exocyst regulators discovered to date include members of the small GTPase family such as Rho, Ral, Rab, and TC10 which are downstream messengers of many signaling pathways (8,19,(27)(28)(29)(30)(31). The establishment of in vitro exocyst reconstitution assay and the availability of exocyst subunit-specific monoclonal antibodies should allow us to further investigate the regulation of exocyst function in response to various intracellular and extracellular signals during development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the multiple, and likely regulated, association of exocyst with various cellular structures may play a role in coordinating protein synthesis, vesicle trafficking and cytoskeletal organization to promote cell growth and cell differentiation. Furthermore, some potential exocyst regulators discovered to date include members of the small GTPase family such as Rho, Ral, Rab, and TC10 which are downstream messengers of many signaling pathways (8,19,(27)(28)(29)(30)(31). The establishment of in vitro exocyst reconstitution assay and the availability of exocyst subunit-specific monoclonal antibodies should allow us to further investigate the regulation of exocyst function in response to various intracellular and extracellular signals during development.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was shown that Rho3 binds to Exo70 in its GTP-bound form (Robinson et al 1999). However, Exo70 mutants that are deficient in Rho3 binding have no defect in exocytosis (He et al 2007a;Hutagalung et al 2009).…”
Section: The Rho Family Of Small Gtp-binding Proteinsmentioning
confidence: 99%
“…Its vector portion was replaced with pRS426 to create MGal-p50-Q24. The expected amino acid sequences of the polyglutamines expressed in this study are as follows: 3HA-Q34, MYPYDVPDYAGYPYDVPDYAGYPYDVPDYAGTQQQK(Q) 31 RDPAS; 3HA-Q80, MYPYDVPDYAGYPYDVPDYAGYPYDVPDYAGTQQ-QK(Q) 77 RDPAS; P50-Q24, MDPYLGRPEQMFHLDGTEKQQQ-K(Q) 21 RDPAS; p50-Q34, MDPYLGRPEQMFHLDGTEKQQQK (Q) 31 RDPAS; and p50-Q80, MDPYLGRPEQMFHLDGTEKQQ-QK(Q) 77 RDPAS. Underlined sequences are epitope tag sequences for anti-p50 antibody.…”
Section: Methodsmentioning
confidence: 98%
“…Cell Staining and Microscopic Analysis-Immunofluorescence of yeast cells was examined using standard procedures (21). Briefly, 0.1 M KPO 4 (pH 6.5) was added to the culture, and then cells (2 ϫ 10 7 ) were fixed with 3.6% formaldehyde.…”
Section: Methodsmentioning
confidence: 99%